Mode use in long-distance travel - Reichert, Alexander; Holz-Rau, Christian (Journal of Transport and Land Use, 2015)
This paper focuses on mode use in long-distance travel. Long-distance travel is responsible for more than 50 percent of climate impact. Nevertheless, it is usually excluded from analyses that examine travel behavior. Whereas studies on daily travel prove that the rural population covers longer distances in daily travel, recent studies (e.g., Holz-Rau, Scheiner, and Sicks 2014; Brand and Preston 2010) show a different picture in long-distance travel. Here, the urban population undertakes more long-distance trips, especially by air. The aim of this paper is to analyze the mode use in long-distance travel in different spatial settings by using multivariate regression models. The (underlying) data derive from a nationwide survey with a sample size of 60,713 respondents, Mobility in Germany 2008 (MiD). A broad range of socio-demographic and socioeconomic characteristics are thereby included as control variables. The results show that even when household income, car accessibility, and education level are considered, the urban population undertakes more long-distance trips, in particular by train and by air. These differences are found in business as well as in private travel.